The didactic value of the sociolinguistic component in scientific dissemination on YouTube - Krpan, Ivana (Didáctica. Lengua y Literatura, 2025)
This study shows the results of the sociolinguistic research of the popular science publications on YouTube and estimates their didactic value in the development of communicative competence in the Spanish language. Its multimodal structure, multidisciplinary approach and lexical-syntactic simplicity capture public’s attention and facilitate comprehension, so they can become a valid teaching resource in the language classroom. This paper analyses the most popular informative vlogs published in the last five years in the peninsular and Canarian variety of Spanish, with the purpose of describing the patterns of the sociolinguistic use of language in the relaxed communicative contexts within the informal register. The qualitative and quantitative analysis addresses three groups of elements: linguistic markers of social relations, expressions of folk wisdom, and markers of informal register. The results show that the analysed videos provide considerable sociolinguistic corpus that correspond to the items proposed by the Council of Europe (2002). The variety and frequency of its use offer new didactic possibilities in the development of communicative competence, both in the field of Spanish as a Foreign Language and Spanish for Specific Purposes, as in public communication of science.